Guidelines for Fieldwork Activities in Environmental Geography: : A Case Study of the East of Thailand - Meksangsouy, Pakorn; Nipithwittaya, Sureeporn; Losiri, Chudech (Journal of Letters, 2020)
Geography is an interdisciplinary subject which can be divided into three areas: physical geography, human geography, and geographical techniques. Fieldwork is considered a crucial element of the fact-discovery process and a path to understanding relationships between the physical dimension and human activities. This paper has two objectives: first, to explore suitable geographical fieldwork sites; second, to create guidelines for geographical fieldwork activities. This paper conducted surveys as the main methodology. All 8 provinces across the East of Thailand were selected as the study area. These provinces are diverse in physical landforms and human activities. The results showed that 23 sites are suitable for environmental geography fieldwork activities. The outcomes of this paper can be divided into two parts; the first outlines the building of a spatial database from fieldwork sites by using the Geographic Information System (GIS) technique. The second part presents an analysis of geographical fieldwork activities. Furthermore, deeper analysis suggests that significant environmental geography knowledge from the fieldwork can be divided into two areas: physical geography and human geography. The former focuses on physical landforms, geology, natural resources, and the environment. The latter involves people-environment relationships from the sites and their surrounding areas. In conclusion, this research explores the importance of geographical studies, fieldwork research and the use of appropriate tools for data acquisition.